Metal-Organic Frameworks as humidity sensor - Schlechte, Laura; Wehring, Bettina; Klein, Nicole; Beese, Harald; Grählert, Wulf; Kaskel, Stefan (Sensoren und Messsysteme 2014 - 17. ITG/GMA-Fachtagung, 2013)
Metal-Organic Frameworks (MOFs), a new class of highly porous materials, have been under intensive research in the last decade. MOFs are based on a modular concept by combining inorganic (metal or metal-oxo-cluster) and organic (multifunctional organic molecules) moieties. Highly porous materials like MOFs show by nature high sensitivity for gas and vapour adsorption due to their very effective adsorption and storage of analytes. Herein we use MOF-materials with open metal sites as humidity sensor. The adsorption/coordination of analytes on those attractive sites leads to a change of the coordination environment and therefore for many transition elements con-taining materials to a colour change in the visible region. Due to the adsorption itself a change of other optical proper-ties like the refractive index are possible and therefore easy to detect using for example spectroscopic methods. More importantly, the uptake and release of guest molecules by porous MOFs as well as its response triggered by external stimuli can directly produce a readable optical signal which is usually even visible with the naked eye. The NIR-analysis, as compared to the UV/Vis analysis, is as well a very promising and more sensitive tool for the detection of water adsorption on MOF-materials at varying relative humidity. The integral intensity of the selected harmonic band of the water molecule can easily be correlated to the humidity level. This work demonstrates the high potential of MOFs serving as a sensor material for the detection of low water vapour concentration (ppm). Thin HKUST-1 MOF-coatings were characterized by FT-NIR and UV/Vis-spectroscopy during the adsorption of water vapour at different concentration levels. For the evaluation of a MOF-based optical humidity sensor, a thin layer of the functional MOF coated on a PET-substrate is placed in a transparent chamber (atm. pressure, 25 °C) connected to a double-pressure humidity generator. The measured UV/Vis/NIR spectra are correlated with the current water vapour concentrations. Using this setup we were able to evaluate the humidity level in a range from 3950 ppm down to 126 ppm.
CRIS-Team Scopus Importer:2023-03-20